2012
DOI: 10.1007/s11999-011-2225-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Total Hip Arthroplasty Using a Transpiriformis Approach: A Preliminary Report

Abstract: Background Continuing efforts have been made to develop minimally invasive surgery techniques for THA. One of the most commonly performed of these techniques is the mini-posterior approach. All reported series using this approach describe surgical detachment of the short external rotators of the hip. In 2008, Penenberg et al. described an innovative surgical technique that preserves the short external rotators. We present the results of a singleincision modification of this technique in 135 patients. Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Many reports have shown that scores after MI THR are as good as those obtained using standard approaches. 3,7,10 Similarly, we observed significant ameliorations in 3-month HHS scores after THR compared to preoperative scores.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Many reports have shown that scores after MI THR are as good as those obtained using standard approaches. 3,7,10 Similarly, we observed significant ameliorations in 3-month HHS scores after THR compared to preoperative scores.…”
Section: Discussionsupporting
confidence: 71%
“…3 Roger and Hill reported mean acetabular cup inclination and anteversion angles of 418 (AE21.498) and 218 (AE15.278), respectively, in 135 cases treated via the posterior MI technique. 7 In our study, the mean acetabular cup inclination was 45.118 (AE7.738) and the mean acetabular anteversion angle was 7.488 (AE9.588); 61 of our cases were within the Lewinnek safe zone. Only one of the remaining 12 cases (outside of the Lewinnek safe zone) had an instability that required revision.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…While the exact etiology of trochanteric pain following hip arthroplasty is often unclear, potential causes include greater trochanteric bursitis or tendinosis of the gluteus medius or minimus tendons [41][42][43]. Recently, several modifications of the posterior approach to the hip (sometimes referred to as "micro-posterior" approaches) have been introduced with the intent of avoiding disruption of the iliotibial band and short external rotators, thus potentially decreasing the incidence of postoperative pain [44,45]. However, the true impact of these modifications requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As minimally invasive surgery technology develops, it had improved the surgical results and reduced the possibility of surgical injury. More and more minimally invasive approaches were being proposed and developed, and minimally invasive technique was the trend of future [1][2][3].…”
Section: Introductionmentioning
confidence: 99%